Three mode polarization-independent (de)multiplexer based on multimode interference coupler. (June 2023) - Hussain, Zaid Lateef; Fyath, Raad S.
Abstract: A polarization-independent, wide-band, three-mode (de)multiplexer is proposed and investigated. The device utilizes a splitter, a phase shifter, and a multi-mode interference (MMI) coupler built into a silicon-on-insulator (SoI) platform. The proposed device is capable of handling six modes TE0/TM0, TE1/TM1, and TE2/TM2, and converting them into uniform fundamental modes TE0/TM0. The device is designed and optimized via numerical simulation using the Rsoft photonics CAD suit. Simulation results indicate that the device has an insertion loss > −0.5 dB, low crosstalk always better than −19 dB, polarization-dependent loss <1 dB, and broad operating bandwidth of 170 nm covering the S, C, and L bands of the optical spectrum. The device is highly fabrication tolerant with a minimum of ±3% from the required value. Such design is suitable for WDM/PDM/MDM hybrid systems to enhance system capacity by a considerable amount.